Diaporthols A and B: Bioactive diphenyl ether derivatives from an endophytic fungus Diaporthe sp. Issue 13 (28th March 2018) - Nakashima, Ken-ichi; Tomida, Junko; Kamiya, Tetsuro; Hirai, Takao; Morita, Yuji; Hara, Hirokazu; Kawamura, Yoshiaki; Adachi, Tetsuo; Inoue, Makoto
Graphical abstract: Highlights: Diaporthe sp. ECN-137 was isolated from the leaves of Phellodendron amurense . Two new diphenyl ethers were found in the fungal culture of Diaporthe sp. ECN-137. New compounds showed anti-migration activities in TGF-β1-elicited MDA-MB-231 cells. Abstract: Diaporthols A (1 ) and B (2 ), two diphenyl ether derivatives, were isolated from cultures of an endophytic fungus Diaporthe sp. ECN-137 obtained from the leaves of Phellodendron amurense . The structures of1 and2 were determined by extensive spectroscopic analyses, and the structure of2 was confirmed by X-ray crystallographic analysis. Compounds1 and2 showed anti-migration activities in TGF-β1-elicited MDA-MB-231 breast cancer cells at a concentration of 20 μM.